STRUCTURE DESIGN OF 61 STORIES REINFORCED-CONCRETE WITH BELT TRUSS AND OUTRIGGER IN JAKARTA - RAJA SURYA SIMAMORA - Nim: 15014147, ADI
The building designed in this final project serves as an office building with 61 stories for upper structure and 6 basement stories as a parking lot with a height up to 273 m above ground level. The office building is located in Jakarta City, having soft soil condition and high seismic acceleration which resulted to the Seismic Design Category D (SDC D). Building designed to be earthquake-resistant using system consisting Special Momen Resisting Frame (SMRF) and Special Structural Wall. The higher a structure then the total drift duet o earthquake will be greater so that required additional structure are belt truss and outrigger. Belt truss and outrigger aim to connect the core system with the perimeter resulting in load transfer and reduced story drift. The construction materials used are reinforced concrete and steel profiles. Structure modeling using software ETABS 2015 with seismic analyisis procedure used is spectrum response analysis. Structure modeling and analysis was performed based on SNI 1726:2012 and ASCE/SEI 7-2010. The design of reinforcement and detailing upper and lower structure are based on SNI 2847:2013 for beams, columns, plates, joint, and shearwall. Beams reinforcement design was excecuted manually based on the forces resulted by software ETABS 2015. Column design using software CSICol to obtain interaction diagram. Shearwall design using software CSICol. And the other structural elemen design manually based on force resulted by software.